Association of sST2 with cardiovascular disease in maintenance hemodialysis patients: A systematic review and meta-analysis - Ze Zhang; Tao Yang; Mengya Zhao; Huaqian Chen (Journal of International Medical Research)
Background Previous studies have shown that soluble growth-stimulated expression gene 2 protein (sST2) plays a significant role in the progression of maintenance hemodialysis. However, the relationship between sST2 and cardiovascular events in maintenance hemodialysis patients remains largely understudied. Method This study systematically searched PubMed, Wanfang, and other Chinese and English databases for all published studies on sST2 in maintenance hemodialysis. Relevant literature meeting the requirements was screened, and relevant data were extracted accordingly. The Newcastle–Ottawa Scale was used to evaluate the quality of the selected studies. Publication bias was assessed via funnel plots and Egger’s test. A meta-analysis was performed using either a random-effects or fixed-effects model, as appropriate. Results A total of 10 high-quality studies were included in this study, with no significant publication bias. The meta-analysis revealed that sST2 level was associated with the incidence of cardiovascular events in maintenance hemodialysis patients (mean difference = 18.89, 95% confidence interval: 13.93–23.84; p   <   0.001). Moreover, elevated sST2 levels were correlated with a higher risk of cardiovascular events (odds ratio = 2.89, 95% confidence interval: 1.71–4.89; p   <   0.0001). Conclusion sST2 may serve as a predictive biomarker for cardiovascular events in maintenance hemodialysis patients.